2001
DOI: 10.1590/s0100-84042001000400009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal-biological aspects on the seed germination of Cucumis anguria L.: influence of the seed coat

Abstract: -(Thermal-biological aspects on the seed germination of Cucumis anguria L.: influence of the seed coat). The seed coat influences the early stages of germination of many seeds and sometimes maintains seed dormancy. Early reports have shown that the testa influences the germination response of Cucumis anguria seeds to light although the response to temperature as influenced by the tegument is not well understood. The main purpose of this study was to observe the influence of the testa on the germination of Cucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(12 reference statements)
0
3
0
3
Order By: Relevance
“…Alguns estudos com espécies vegetais nativas têm mostrado que a velocidade de germinação depende das condições de incubação das sementes (Lima et al 1997, Santos & Cardoso 2001. O efeito da temperatura no tempo médio de germinação (F = 280,17, P = 0,00) foi Figura 1.…”
Section: Resultsunclassified
“…Alguns estudos com espécies vegetais nativas têm mostrado que a velocidade de germinação depende das condições de incubação das sementes (Lima et al 1997, Santos & Cardoso 2001. O efeito da temperatura no tempo médio de germinação (F = 280,17, P = 0,00) foi Figura 1.…”
Section: Resultsunclassified
“…Nesse sentido, poucos são os estudos (ALMEIDA et al, 2019;SANTOS;CARDOSO, 2001) buscando avaliar as condições térmicas para determinação da qualidade fisiológica por meio do teste de germinação em sementes de maxixe, cuja cultivar "Do Norte" tem sido alvo de estudo. Entretanto, não há na literatura pesquisas com sementes de maxixe da cultivar Liso Gibão.…”
Section: Introductionunclassified
“…They also refl ect the physiological and morphological features of the seeds prior to germination, since they can be altered by specifi c treatments before the germination tests (Vegis 1963). Santos & Cardoso (2001), for instance, found that seed coat cane interfere with the themal responses related to seed germination of Cucumis anguria.…”
Section: Introductionmentioning
confidence: 99%